The Effectiveness of Chain Drill Technique in Developing Students' Speaking Skill - Haniefah, Hilwa; Rahmawati, Eulis; Rohman, Rohman (Program Studi Magister Tadris Bahasa Inggris UIN Sultan Maulana Hasanuddin Banten, 2024)
This research designed to find out students' speaking skills before and after using the chain drill technique and to find out how the effectiveness of chain drill in developing students' speaking skills at the eighth grade students of SMPN 9 Cilegon. The researcher collected the data from 62 students divided into two classes, one class as the experimental class and another one as the control class, by applying experimental research method. The population is the eighth grade students of SMPN 9 Cilegon, while class VIII-D as the experimental class and class VIII-C as the control class are taken as the sample. Differences in students before being given treatment and the condition of students after being given treatment, namely Based on the explanation above, it can be seen that the results of the post-test in the experimental class experienced a significant increase after being given treatment, seen from the average post test better than the average pre-test is 64.38 < 80,91. The results of the hypothesis, the degree of significance is 5% and 1%. Therefore, to:tt= 4,48>1.67, in degree of significance 5% and to:tt = 4,48>2.38 in degree of significance 1%. Shows that the use of the chain drill technique is effective in developing the speaking skills of students in class VIII-D of SMPN 9 Cilegon.